2011
DOI: 10.1074/jbc.m111.311530
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmotic Stress Induces Aquaporin-dependent Cell Shrinkage, Polyphosphate Synthesis, Amino Acid Accumulation, and Global Gene Expression Changes in Trypanosoma cruzi

Abstract: Background: Trypanosoma cruzi is subjected to hyperosmotic stress during its life cycle. Results: The recovery from hyperosmotic stress involves the function of an aquaporin, amino acid accumulation, polyphosphate synthesis, and global gene regulation. Conclusion:The response to hyperosmotic stress is different from that observed in mammalian cells or yeasts. Significance: Learning the mechanism of osmoregulation is important for finding new drug targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 45 publications
7
74
0
Order By: Relevance
“…Content-Previous studies demonstrated that polyP is important for trypanosome growth and osmoregulation in trypanosomes (22,23,27,30,31,37), but the length of the polyP responsible for these roles was not investigated. To investigate whether the short chain polyP synthesized by TbVtc4 is involved in these processes, we analyzed the phenotypic changes of BSF trypanosomes with a conditional KO of TbVtc4.…”
Section: Reduced Expression Of Tbvtc4 In Bsf Trypanosomes Results In mentioning
confidence: 99%
See 4 more Smart Citations
“…Content-Previous studies demonstrated that polyP is important for trypanosome growth and osmoregulation in trypanosomes (22,23,27,30,31,37), but the length of the polyP responsible for these roles was not investigated. To investigate whether the short chain polyP synthesized by TbVtc4 is involved in these processes, we analyzed the phenotypic changes of BSF trypanosomes with a conditional KO of TbVtc4.…”
Section: Reduced Expression Of Tbvtc4 In Bsf Trypanosomes Results In mentioning
confidence: 99%
“…PolyP hydrolysis occurs during hyposmotic stress of trypanosomes (22), probably increasing the osmotic pressure of the acidocalcisomes and facilitating water movement. On the other hand, an increase in long chain polyP levels has been observed in T. cruzi during hyperosmotic stress (22,23). This latter work suggested that polyP could play an important role at the early stages of hyperosmotic stress response by sequestering ions into the acidocalcisomes to reduce the ionic strength of the cytosol (23).…”
mentioning
confidence: 93%
See 3 more Smart Citations